1965
DOI: 10.1002/jctb.5010150703
|View full text |Cite
|
Sign up to set email alerts
|

The emission of corrosive vapours by wood. I. Survey of the acid‐release properties of certain freshly felled hardwoods and softwoods

Abstract: The importance has been assessed of various factors responsible for the release of corrosive vapours from certain freshly‐felled hardwood and softwood species on exposure to high humidity and temperatures in excess of 30°. Variables studied include (i) season of felling, (ii) differences between sapwood and heartwood regions, (iii) initial acid content of the timber on felling, (iv) rǒle of non‐volatile extractive components in catalysing release of corrosive vapours and (v) inhibition of enzymic reactions by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1965
1965
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Furthermore, when Terminalia ivorensis was extracted with a mixture of ethanol and water, it was much less corrosive. Similarly, Arni et al [17] removed all of the volatile acids and phenolics from the wood and found the extracted wood was not corrosive toward mild steel.…”
Section: Small Organic Acidsmentioning
confidence: 99%
“…Furthermore, when Terminalia ivorensis was extracted with a mixture of ethanol and water, it was much less corrosive. Similarly, Arni et al [17] removed all of the volatile acids and phenolics from the wood and found the extracted wood was not corrosive toward mild steel.…”
Section: Small Organic Acidsmentioning
confidence: 99%
“…The size of the calcium hydroxide particles was checked by XRD measurements on dry nanoparticles powder and by SAXS on a 2% w/w dispersion of Ca(OH) 2 in 2-propanol. Dimension of the crystallites were deduced from the width of diffraction peaks in the XRD pattern, using the Scherrer equation: 0.89 = L·(B [2]·cos), where B(2) is the width of the X-ray pattern line at half peakheight in radians; is the wavelength of X-ray (1.54 Å for Cu K␣ was used); is the angle between incident beams in degrees, and L is the crystallite size of the powder samples in Å. We calculated L from each of the main diffraction peaks of calcium hydroxide ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The organ wind systems are largely made from wood. Wood is known to emit a variety of organic vapors, such as acetic and formic acid and aldehydes [2,3]. Laboratory studies show that low concentrations (170-1100 ppb) of acetic and formic acid vapor in humid air are very corrosive towards lead [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Wood materials are known to emit acetic acid vapor as a function of cellulose hydrolysis. (11) The extent of the vapor emission can be a function of the initial acetic acid concentration as well as cellulose concentration. (12) The impact of the acetic acid vapor emission on the corrosion of lead is widely known and addressed in the museum and artifact industry since the preservation of lead artifacts in wood casings has resulted in extensive corrosion.…”
Section: Cane-fiberboard (Cf)mentioning
confidence: 99%